METODE ISTINBATH IMAM ASY- SYATIBI - Asep Hedi Turmudi (IAIN TERNATE, 2017)
Among the people of the islamic law that slightly above, scholars who tried to seriously formulate and practicing being patterned istiqra ' ma`nawi .She looked that Islamic law juz' yeah a particular are built on the principle law ( universal ), and - law kulliyah were obtained through survey extend to law, by using the method being patterned istiqra specific he described by method a l-istiqr a ' a l-ma nawi